UTILIZING ARTIFICIAL INTELLIGENCE FOR PLANT SPECIES IDENTIFICATION AND CLASSIFICATION IN BOTANICAL RESEARCH - Jaipal Dhobale,; Justin R Nayagam,; Angeline Christobel Y,; Mallu Mallikarjuna,; Samarth.H.Bharadwaj,; Sumayya Abdul Rahim,; Deepika Lodha, (The Bioscan, 2025)
The rapid growth of the artificial intelligence (AI) has mainly had revolutionized many fields, including the botanical research. The article mentions AI as an important tool in finding and labeling plant species, which is a major aspect in botanical studies, conservation and agricultural cultivation. With the implementation of machine learning algorithms in plant image recognition it is now possible to automated and improve user accuracy regarding what is known as the plant species recognition problem that was once implemented by botanists. The paper outlines the various AI methods of plant species recognition neural networks (CNNs) and other AI models, their applications, pros and cons. The outcome of the new study articulates the excellence of the AI-related systems compared to the traditional ones which are concerned with prompt and sounder identifications. But there is limited data, voluminous amount of data is needed to train the models and finally there is generalization of the model which are grave issues. The paper presents the potentiality of AI in the future in botanical studies and conservation and how it is likely to be utilized in the future, when it is integrated with other systems like remote sensing.